PIWI-interacting RNAs: who, what, when, where, why, and how - Haase, Astrid D; Ketting, Rene F; Lai, Eric C; van Rij, Ronald P; Siomi, Mikiko; Svoboda, Petr; van Wolfswinkel, Josien C; Wu, Pei-Hsuan (The EMBO journal, 2024)
PIWI-interacting RNAs (piRNA) suppress selfish genetic elements and are essential for germ cell biology in animals. They also play critical roles in regeneration in planaria, regulate gene expression in adult mammalian testes, and participate in antiviral defense in mosquitoes. Inspired by a recent workshop on PIWI proteins and piRNAs, this commentary aims to summarize fundamental aspects of piRNA biology, highlight recent advances, and discuss key outstanding questions. It is written by and for biochemists, geneticists, and evolutionary biologists, and represents our interdisciplinary perspective.